Clinico-demographic profile among female with alcohol related problems in the eastern part of Nepal - Gautam Joshi, Rinku; Koirala, P; Shakya, DR; Shyangwa, PM (Health Renaissance, 2017)
Background: Alcohol can affect anyone. It is not prejudicial towards any race, colour, sex, religion or economic level. It affects individual’s life, personal relationship, health and occupational functioning.1 Alcohol is estimated to cause a net harm of 3.7% of all deaths and 4.4% of the global burden of disease.3 This study will provide baseline data and pave way for further studies and broaden the implication for the management and control of alcohol related problems in female. Objective: To provide baseline data about the clinico-demographic profile of the female with alcohol related problems. Method: A semi- structured proforma was designed to collect the data. A total of 51 female patients participated in the study after giving their written informed consent. Result: The maximum number of patients were in the age group of 41-50 (37.2%); followed by the age group 31-40 (31.3%). The mean age was 42.63 ± 11.11 years. The predominant caste was Rai 33.3% followed by Limbu 19.6%. All the cases were Hindus by religion. Most of the cases were married (82.3%) housewives, (56.8%) with nuclear family (68.6%) and illiterate (58.8%). The age of first alcohol intake was 17.45±9.45 years, total duration of use 24.86±14.7. Family custom (56.88%) was the most common reason for the first use of alcohol. Local distilled alcohol was preferred (58.8%) and 72.5% used to drink alone. The most common presenting complaint was auditory hallucination (12.36%). Conclusion: The most affected age group was at the peak of their economic and reproductive abilities. Most of the patients were illiterate and jobless. A comprehensive educational awareness program about alcohol use and its effects on the female as a whole, with special attention to pregnancy and lactation is to be undertaken at the community level, with maximum female participation. It is important to recognize and realize that women have unique aspects to their alcohol problems and to understand the complex interplay of roles they have to play in the form of daughter, mother, wife, in-law and manager of the household activities including taking care of children as well as elderly at home and plan accordingly. Health Renaissance 2015;13(2): 30-42